THE CONCEPT OF «WARRIOR» IN THE LINGUISTIC WORLD VIEW OF UKRAINE AND SPAIN IN THE 21st CENTURY - Smorokova , Elina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article provides an in-depth examination of the evolving concept of “warrior” during Russian aggression in Ukraine. It highlights the paramount importance of cognitive linguistics in unravelling the ways in which language shapes and is shaped by our beliefs, particularly in times of social and political unrest. Based on an analysis of Ukrainian and Spanish media, this study highlights the significant impact of cultural and cognitive frameworks on the communication of concepts in language. This understanding provides an essential basis for a comprehensive study of the development of the concept in different cultural and linguistic contexts. The research definitively establishes the importance of cultural influences in shaping linguistic expressions and, consequently, worldviews and ideologies. It also reinforces the idea that language is not just a means of communication, but a powerful tool for propaganda, persuasion, and the construction of national identities. The use of Ukrainian and Spanish media as analytical focal points allows for a cross-cultural and cross-linguistic comparison, enhancing our understanding of how the notion of a ’warrior’ is perceived and represented in these unique contexts. The article offers an insightful perspective that sheds light on the complex interplay between language, culture and evolving social dynamics. _____________ References: • Vil’chyns’ka, T. Verbalizacija binarnoi’ konceptual’noi’ opozycii’ “zahysnyk – vorog” (na materiali gazetnyh tekstiv) [Verbalization of the binary conceptual opposition "defender – enemy" (based on newspaper texts)]. Mediaprostir10 (2017): 59–65. • 2Vil’chyns’ka, T. Koncept – vijna: osoblyvosti movnoi’ ob’jektyvacii’ u gazetnomu teksti [The concept of war: features of linguistic objectification in a newspaper text]. Linguistic Studies34 (2017): 110–114. • Kyryljuk, Zmistove napovnennja leksyko-semantychnoi’ grupy “voi’ny” v dyskursi rosijs’ko-ukrai’ns’koi’ vijny [Content of the lexical and semantic group "warriors" in the discourse of the Russian-Ukrainian war]. Academic studies. Series “Humanities” 2 (2022): 90–96. • Koval’ova, Opozycija “svij – chuzhyj” pry formuvanni nacional’noi’ identychnosti v konteksti globalizacii’. [Opposition “friend or foe” in the formation of national identity in the context of globalisation]. Scientific Notes. Series “Philosophy” 5 (2009): 84–91. • Pidkaminna, L. V. Modeljuvannja konceptu “voi’n” u suchasnyh ukrai’ns’kyh ZMI Modelling the concept of “warrior” in modern Ukrainian media]. Scientific Journal of the Drahomanov National Pedagogical University. Series 8. Philological Sciences7 (2017): 105–111. • Porshnev, B. F. Ponjatyja “para” y “chuzhye” v socyal’noj psyhologyy The concepts of “couple” and “strangers” in social psychology]. Theses of the 2nd International Colloquium on Social Psychology (1970): 14-18. • Pochepcov G. Kognytyvnye vojny v socmedya, massovoj kul’ture y massovyh kommunykacyjah. [Cognitive wars in social media, mass culture and mass communications] (Kharkiv: Folio, 2019), 314. • Fabiszak, М. A Conceptual Metaphor approach to war discourse and its implications (Poznan: WydawnictwoNaukowe UAM, 2007) • Goriacheva, D. Understanding the “Ukrainian Crisis.” Metaphors used by Ukrainian, German, and British Leaders in 2014-16. Ideology and Politics 1 (6) (2016): 86˗152. • Smoor, L. Understanding the Narratives Explaining the Ukrainian Crisis: Identity Divisions and Complex Diversityin Ukraine. Acta Universitatis Sapientiae, European and Regional Studies 11 (1) (2017): 63˗96.